2011
DOI: 10.1007/s11269-011-9877-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Green Roofs on Runoff Water Quality: A Case Study from Estonia

Abstract: This paper describes the runoff water quality of Light Weight Aggregates (LWA)-based extensive green roofs and sod roofs in Estonia. Samples were taken from August 2004 to April 2009 from 10 different green roofs to determine what level of water quality may be found. The results presented here show that green roofs influenced water quality to a considerable degree. The runoff water of LWA-based green roofs generally had higher values of pH, BOD 7 , TP and PO 4 -P than that from sod roofs. However, COD, TN, SO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 24 publications
1
39
2
4
Order By: Relevance
“…In the opinion of the authors, the release of total nitrogen and phosphates from the surface of green roofs can be related to additional fertilisation, as the application of conventional fertilisers contributes to increased concentration of various forms of nitrogen and phosphorus in the runoff waters. Therefore, care should be taken to use fertilisers with controlled rate of nutrient release [42]. In an experiment conducted within the scope of a study on the chemistry of rain waters, MacAvoy [4] demonstrated, for 9 rainfall events, the occurrence of higher concentrations of NO 3…”
Section: Resultsmentioning
confidence: 99%
“…In the opinion of the authors, the release of total nitrogen and phosphates from the surface of green roofs can be related to additional fertilisation, as the application of conventional fertilisers contributes to increased concentration of various forms of nitrogen and phosphorus in the runoff waters. Therefore, care should be taken to use fertilisers with controlled rate of nutrient release [42]. In an experiment conducted within the scope of a study on the chemistry of rain waters, MacAvoy [4] demonstrated, for 9 rainfall events, the occurrence of higher concentrations of NO 3…”
Section: Resultsmentioning
confidence: 99%
“…Most of the previous studies concentrate on the monitoring of green roof runoff quality [7,[9][10][11]14], not on substrate chemical composition. In some exceptions, e.g., [64], substrate mix components are analyzed for chemical composition but phosphorus, which excess loads have the potential to increase eutrophication risk for lakes and rivers, is not included.…”
Section: Discussionmentioning
confidence: 99%
“…Tema (Alsup et al, 2011;Beck et al, 2011;Buccola & Spolek, 2010;Hathaway et al, 2008;uoppamäki & Lehvävirta, 2016;Malcolm et al, 2014;Mendez et al, 2011;Razzaghmanesh et al, 2014;Schwager et al, 2014;Seidl et al, 2013;Teemusk & Mander, 2011;Vijayaraghavan & Raja, 2014;Vijayaraghavan & Raja, 2015) Influencia en la calidad de la escorrentía tratada asociada a distintas mezclas de componentes del sustrato como gravas, vermiculita y carbón vegetal, entre otros.…”
Section: Referenciaunclassified